2005
DOI: 10.1111/j.1365-2222.2005.02156.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor association between allergen‐specific serum immunoglobulin E levels, skin sensitivity and basophil degranulation: a study with recombinant birch pollen allergen Bet v 1 and an immunoglobulin E detection system measuring immunoglobulin E capable of binding to FcɛRI

Abstract: Our results highlight the quantitative discrepancies and limitations of the present diagnostic tools in allergy, even when using a single allergenic molecule. The quantity of allergen-specific serum IgE is only one component of far more complex cellular systems (i.e. basophil-based tests, skin tests) used as indirect diagnostic tests for IgE-mediated allergic sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 28 publications
4
32
1
1
Order By: Relevance
“…Some papers reported that antigen-specific IgE levels were poorly associated with skin sensitivity and basophil degranulation (Conroy et al, 1977;Dembo and Goldstein, 1978;Malveaux et al, 1978;Purohit et al, 2005), and mast cells were activated by IgE-independent pathways (Tatemoto et al, 2006), these results support current results.…”
Section: Discussionsupporting
confidence: 82%
“…Some papers reported that antigen-specific IgE levels were poorly associated with skin sensitivity and basophil degranulation (Conroy et al, 1977;Dembo and Goldstein, 1978;Malveaux et al, 1978;Purohit et al, 2005), and mast cells were activated by IgE-independent pathways (Tatemoto et al, 2006), these results support current results.…”
Section: Discussionsupporting
confidence: 82%
“…This result disagrees with the study of Purohit et al [12] who showed that the concentration of allergen-specific IgE antibodies capable of binding to FcεRI and biological sensitivities were not necessarily associated. However, it is in agreement with the study of McDermott et al [46] who stated that the ability of Ara h 2 to effectively cross-link IgE from a specific serum was related to the proportion of anti-Ara h 2 antibodies in that serum.…”
Section: Discussioncontrasting
confidence: 57%
“…By ELISA, one epitope is sufficient to obtain reactivity, and thus this could lead to false-positive results in the identification of relevant allergens that are biologically active. Additionally, parameters such as the ability of the IgE to bind its receptor or the binding affinity are not taken into account by ELISA [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…For a few sera, the antibody levels and biological activity were not associated (i.e. A2, A7, A29), but this phenomenon has already been described for several allergens including Der p 1 and Der p 2 [7,35,36]. Several factors such as the number and geometry of IgE epitopes as well as affinity/avidity of IgE binding may influence the mediator release activity.…”
Section: Discussionmentioning
confidence: 99%